PERKEMBANGAN PENDIDIKAN ISLAM PADA PONDOK PESANTREN - Fitriyyah, Rofii’atul (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
Islamic boarding schools are often referred to as Islamic educational institutions and at the same time are community service institutions that are considered unique and different from other educational institutions. The history of the growth and development of Islamic boarding schools shows that it has a strong base in the Muslim community. This is because pesantren is an indeginous institution of the archipelago that is firmly rooted in the society that surrounds it. In the second half of the 20th century, pesantren experienced development, this was because the learning system began to develop into a school or madrasah system, without leaving the conventional system, namely the sorogan and bandongan systems. In the early stages, pesantren prepares its students as Islamic religious teachers or as informal leaders (kyai). In the world of Islamic boarding schools, the term "Five Souls" of Islamic Boarding Schools and the Five Basic Elements of a Islamic Boarding School is famous. For the Five Souls of Islamic Boarding Schools, which consist of the Soul of Sincerity, the Soul of Simplicity, the Soul of Ukhuwah Islamiyyah, the Soul of Independence and the Soul of Freedom